The role of mitochondria in eosinophil function: implications for severe asthma pathogenesis - Koranteng, Janice; Chung, Kian Fan; Michaeloudes, Charalambos; Bhavsar, Pankaj (Frontiers in Cell and Developmental Biology, 2024)
Mitochondria are key metabolic hubs involved in cellular energy production and biosynthesis.ATP is generated primarily by glucose and fatty acid oxidation through the tricarboxylic acid (TCA) cycle and oxidative phosphorylation (OXPHOS) in the mitochondria. During OXPHOS there is also production of reactive oxygen species (ROS), which are involved in the regulation of cellular function. Mitochondria are also central in the regulating cell survival and death, particularly in the intrinsic apoptosis pathway. Severe asthma is a heterogeneous disease driven by various immune mechanisms. Severe eosinophilic asthma entails a type 2 inflammatory response and peripheral and lung eosinophilia, associated with severe airflow obstruction, frequent exacerbations and poor response to treatment. Mitochondrial dysfunction and altered metabolism have been observed in airway epithelial and smooth muscle cells from patients with asthma. However, the role of mitochondria in the development of eosinophilia and eosinophil-mediated inflammation in severe asthma is unknown. In this review, we discuss the currently limited literature on the role of mitochondria in eosinophil function and how it is regulated by asthma-relevant cytokines, including interleukin (IL)-5 and granulocytemacrophage colony-stimulating factor (GM-CSF), as well as by corticosteroid drugs. Moreover, we summarise the evidence on the role of mitochondria in the regulation of eosinophils apoptosis and eosinophil extracellular trap formation. Finally, we discuss the possible role of altered mitochondrial function in eosinophil dysfunction in severe asthma and suggest possible research avenues in order to better understand their role in disease pathogenesis, and identify novel therapeutic targets.